Assessing Motor Performance and Ankle Mobility in Pre-Adolescent Male Fencers - Yalcin Aydin; Gurkan Tokgoz; Nurkan Yilmaz; Ilgin Ali Coskun; Aysegul Beykumul; Enes Colak; Caner Aygoren; Samet Koc; Fahri Safa Cinarli (Life)
Ankle mobility plays a critical role in dynamic stability and propulsion during fencing-specific actions. However, its relationship to performance metrics in young athletes remains unclear. This study aimed to investigate the relationship between ankle range of motion (ROM), acceleration, and jump height in pre-adolescent male fencers, as well as to examine bilateral differences in ankle mobility between the front and rear foot. Fifteen fencers (age 10.86 ± 0.91 years) were assessed for ankle ROM (dorsiflexion, plantar flexion, inversion, eversion) using a goniometer. Performance tests included a 7 m sprint lunge (acceleration) and countermovement jump. Significantly large correlations were observed between front and rear foot ankle plantar flexion range of motion and both acceleration (r = 0.625–0.628, p < 0.05) as well as vertical jump height (r = 0.579–0.647, p < 0.05). Rear foot ankle plantar flexion range of motion significantly predicted acceleration (r2 = 0.335, p < 0.05) and jump height (r2 = 0.418, p < 0.05). In contrast, no meaningful associations were found between dorsiflexion, inversion, or eversion range of motion and performance metrics. Additionally, bilateral comparisons revealed significantly greater dorsiflexion in the front foot ankle and greater eversion in the rear foot ankle (p < 0.05). Plantar flexion ROM is a key contributor to acceleration and jump capacity in youth fencers. Incorporating ankle mobility training may support physical development in this population.